2021
DOI: 10.1038/s41598-021-88377-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies on induced ferromagnetism of new (1 − x)Na0.5Bi0.5TiO3 + xBaFeO3−δ solid solution

Abstract: New solid solution of Na0.5Bi0.5TiO3 with BaFeO3−δ materials were fabricated by sol–gel method. Analysis of X-ray diffraction patterns indicated that BaFeO3−δ materials existed as a well solid solution and resulted in distortion the structure of host Na0.5Bi0.5TiO3 materials. The randomly incorporated Fe and Ba cations in the host Na0.5Bi0.5TiO3 crystal decreased the optical band gap from 3.11 to 2.48 eV, and induced the room-temperature ferromagnetism. Our density-functional theory calculations further sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 91 publications
(80 reference statements)
2
7
1
Order By: Relevance
“…As we have seen, the non‐spin polarization emerges around the Fermi‐level, implying that the perfect BNT (110) surface is non‐magnetic because there is no unpaired electron. The result is consistent with theoretical and experimental studies on BNT (100) surface by Ju et al 10,11 and also agrees with bulk BNT 13,15,27 …”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…As we have seen, the non‐spin polarization emerges around the Fermi‐level, implying that the perfect BNT (110) surface is non‐magnetic because there is no unpaired electron. The result is consistent with theoretical and experimental studies on BNT (100) surface by Ju et al 10,11 and also agrees with bulk BNT 13,15,27 …”
Section: Resultssupporting
confidence: 92%
“…10 The calculation for surface energy among the (010), (100), (101) and (111) surfaces indicated that the (100) surface is the most stable of the four kinds of surfaces. 11 However, the calculation for the (100) BNT surface direction was not consistent with the experimental results given in Refs [10][11][12][13][14][15], where the BNT (110) direction was favoured for crystal growth. Thus, we suggested that the observed room-temperature ferromagnetism in BNT materials could be contributed by BNT (110)-surface defects rather than that of (100)-surface defects.…”
Section: Introductioncontrasting
confidence: 61%
See 3 more Smart Citations